Update on the Biology, Management, and Treatment of Small Cell Lung Cancer (SCLC) - Saltos, Andreas; Shafique, Michael; Chiappori, Alberto (Frontiers in Oncology, 2020)
Small-cell lung cancer (SCLC) accounts for 13-15% of all new lung cancer cases in the US. The tumor has a tendency to disseminate early resulting in 80-85% of patients being diagnosed with extensive disease (ES-SCLC). Chemotherapy has provided SCLC patients considerable survival benefits over the past 3 decades. Nonetheless most patients relapse and rarely survive beyond 2 years. Despite consistent overall response rates of ≥ 50%, until recently, median survival times and 2-year survivals only ranged between 7-10 months and 10-20%, respectively. Several chemotherapy agents possess activity against SCLC, both, as single agents and in combinations but etoposide-platinum emerged as the preferred first line regimen. Upon relapse, many patients remain candidates for additional therapy. However, the sensitivity of relapsed SCLC to further therapies is markedly reduced and dependent upon the level and duration of response to the initial treatment (platinum-sensitive vs. resistant relapse). Multiple factors suggest a therapeutic role for immunotherapy in SCLC: (1) SCLC has been associated with immune-mediated paraneoplastic processes (cerebellar degeneration, limbic encephalitis and Lambert-Eaton syndrome) and patients presenting with these paraneoplastic syndromes have shown more favorable outcomes, suggesting an underlying immune response mechanism. (2) Comprehensive genomic profiling of SCLC indicates that the majority lack functional p53 (90%) and Rb1 (65%). These universal genetic aberrations facilitate poor genomic stability, thus perpetuating the generation of tumor associated antigens, amenable to targeting with immunotherapy. (3) SCLC has one of the highest mutational loads, likely a reflection of the myriad of insults inflicted by smoking-related carcinogens. The relationship between tumor mutational load and response to immune checkpoint inhibitors has been established in multiple solid tumors, including preliminary results in relapsed SCLC. In this manuscript, we review the early (some failed and discontinued, some partly successful and still ongoing) attempts to incorporate immunotherapy (particularly vaccine based approaches) to the treatment of SCLC, and the latest attempts (mostly incorporating the use of checkpoint inhibitors), including those with favorable but preliminary results (CheckMate 032, Keynote 028 and 158), and those with more definitive positive (iMpower 133 and CASPIAN) and negative (CheckMate 331 and 451) results.